T Lymphocytes and Cytokines: Earlier time to peak indicates better prognosis in COVID-19 patients? - Siyuan Gao; Junyi Li; Yan Zhang; Huiming Liu; Xiaodong Yang; Ting Jia; Fangrong Zhang; Xiuling Zhang; Jianpeng Gao (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2021)
Aims: To explore the changes of cytokines and T lymphocyte subgroups in COVID-19 patients, to find the turning point to severe clinical course of patients, to timely intervene, and to reduce the severity.  Methods: Thirty-nine patients with COVID-19 admitted to Third People's Hospital of Kunming from January 31, 2020 to March 2, 2020 were divided into 3 groups: mild, common and severe/critical according to 'Clinical Protocol for COVID-19, 8th Edition' (National Health Commission of People's Republic of China). The changes of serum T lymphocyte subgroups and cytokines level during hospitalization were monitored and statistically analyzed.The difference was considered statistically significant when p< 0.05.  Results: 39 patients with COVID-19 were 41.51±19.03 years old, 18 of them were male (46.2%).8 patients (20.5%) were classified as mild group, 10 patients (25.6%) were classified as common group, 21 patients (53.8%) were classified as severe/critical group. The hospitalization days were 17.51±6.19 days, and the nucleic acid seroconversion days from positive to negative were 11.41±6.77 days. Comparison of T lymphocyte subgroups in patients with different clinical classifications showed that T cell count and CD4/CD8+T cell counts were different among different clinical classifications (p< 0.05). In pairwise comparison, the count of lymphocyte subgroups in severe/critical group patients was significantly lower than that in mild and common groups. Intra-group Comparison showed that, IL-2, IL-8, IL-12p70 and IL-5 examinations had significant statistical differences at different examination time points, but the effects of the above indicators on clinical classification would not change with time. According to develop trends, lymphocytes increased in patients of three clinical groups after treatment, the increase trends were obvious especially in severe/critical group patients.The OR value calculated by Logistics model showed that the probability of severe/critical disease was 1.276 times higher for each day increase of T cell time to peak (95%CI: 1.039-1.569), χ2= 5.379, p= 0.02.The probability of severe/critical disease was 1.408 times (95%CI: 1.066-1.859) with each day increase of IL1β time to peak, χ2 = 5.824, p= 0.016. Independent sample t test showed that in CD4+T cells, IL-1β, IL-2, IL-8, IL-12p70, IL-17A, IFN-γ, TNF-α and other detection indicators, the time to peak of the above indicators in the fast seroconversion group was significantly shorter than that in slow seroconversion group.  Conclusions: The early peak, timely decrease of cytokines and T cell counts in COVID-19 patients has a positive effect on prognosis. Cytokines and T cell counts should be closely monitored in COVID-19 patients.